A prospective evaluation of first people's health promotion program design in the goulburn-murray rivers region - Joyce Doyle; Sharon Atkinson-Briggs; Petah Atkinson; Bradley Firebrace; Julie Calleja; Rachel Reilly; Margaret Cargo; Therese Riley; Tui Crumpen; Kevin Rowley (BMC, 2016)
Abstract Background Aboriginal Community Controlled Organisations (ACCOs) provide community-focussed and culturally safe services for First Peoples in Australia, including crisis intervention and health promotion activities, in a holistic manner. The ecological model of health promotion goes some way towards describing the complexity of such health programs. The aims of this project were to: 1) identify the aims and purpose of existing health promotion programs conducted by an alliance of ACCOs in northern Victoria, Australia; and 2) evaluate the extent to which these programs are consistent with an ecological model of health promotion, addressing both individual and environmental determinants of health. Methods The project arose from a long history of collaborative research. Three ACCOs and a university formed the Health Promotion Alliance to evaluate their health promotion programs. Local community members were trained in, and contributed to developing culturally sensitive methods for, data collection. Information on the aims and design of 88 health promotion activities making up 12 different programs across the ACCOs was systematically and prospectively collected. Results There was a wide range of activities addressing environmental and social determinants of health, as well as physical activity, nutrition and weight loss. The design of the great majority of activities had a minimal Western influence and were designed within a local Aboriginal cultural framework. The most common focus of the activities was social connectedness (76 %). Physical activity was represented in two thirds of the activities, and nutrition, weight loss and culture were each a focus of about half of the activities. A modified coding procedure designed to assess the ecological nature of these programs showed that they recruited from multiple settings; targeted a range of individual, social and environmental determinants; and used numerous and innovative strategies to achieve change. Conclusion First Peoples' health promotion in the Goulburn-Murray Rivers region encompasses a broad range of social, cultural, lifestyle and community development activities, including reclaiming and strengthening cultural identity and social connectedness as a response to colonisation.